Impaired Adipogenesis Caused by a Mutated Thyroid Hormone α1 Receptor - Ying, Hao (American Society for Microbiology, 2007)
Thyroid hormone (T3) is critical for growth, differentiation, and maintenance of metabolic homeostasis. Mice with a knock-in mutation in the thyroid hormone receptor α gene (TRα1PV) were created previously to explore the roles of mutated TRα1 in vivo. TRα1PV is a dominant negative mutant with a frameshift mutation in the carboxyl-terminal 14 amino acids that results in the loss of T3 binding and transcription capacity. Homozygous knock-in TRα1(PV/PV) mice are embryonic lethal, and heterozygous TRα1(PV/+) mice display the striking phenotype of dwarfism. These mutant mice provide a valuable tool for identifying the defects that contribute to dwarfism. Here we show that white adipose tissue (WAT) mass was markedly reduced in TRα1(PV/+) mice. The expression of peroxisome proliferator-activated receptor γ (PPARγ), the key regulator of adipogenesis, was repressed at both mRNA and protein levels in WAT of TRα1(PV/+) mice. Moreover, TRα1PV acted to inhibit the transcription activity of PPARγ by competition with PPARγ for binding to PPARγ response elements and for heterodimerization with the retinoid X receptors. The expression of TRα1PV blocked the T3-dependent adipogenesis of 3T3-L1 cells and repressed the expression of PPARγ. Thus, mutations of TRα1 severely affect adipogenesis via cross talk with PPARγ signaling. The present study suggests that defects in adipogenesis could contribute to the phenotypic manifestation of reduced body weight in TRα1(PV/+) mice.